2020
DOI: 10.1111/ene.14182
|View full text |Cite
|
Sign up to set email alerts
|

Is scan‐negative cauda equina syndrome a functional neurological disorder? A pilot study

Abstract: BACKGROUNDCauda equina syndrome (CES) is a neurosurgical emergency which warrants a lumbar MRI. Many patients with suggestive symptoms of CES have no radiological correlate. A functional (non-organic) aetiology has been proposed in some, but currently little is known about this patient group and their clinical outcomes. METHODSAt a tertiary referral centre, 155 adult patients underwent urgent lumbar MRI for suspected CES in one year from December 2014. Data regarding clinical symptoms and follow-up were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Around two-thirds of patients presenting with symptoms of sphincter dysfunction with or without leg weakness and pain have normal imaging or lumbar root changes that don't explain retention. 32,33 Patients with negative scans were found to commonly have positive features of FND, such as Hoover's sign. Factors such as pain, medications (particularly opiates) and pre-existing bladder disorders may all explain these common neurosurgical presentations.…”
Section: Urinary Retention and 'Scan-negative' Cauda Equina Syndromementioning
confidence: 99%
“…Around two-thirds of patients presenting with symptoms of sphincter dysfunction with or without leg weakness and pain have normal imaging or lumbar root changes that don't explain retention. 32,33 Patients with negative scans were found to commonly have positive features of FND, such as Hoover's sign. Factors such as pain, medications (particularly opiates) and pre-existing bladder disorders may all explain these common neurosurgical presentations.…”
Section: Urinary Retention and 'Scan-negative' Cauda Equina Syndromementioning
confidence: 99%
“…However, the frequency of co-morbid depression in a cohort of patients following surgery for CES has rarely been described; Gibson et al reported this to be present in only 8% (n = 2), whereas Hoeritzauer et al described a frequency of 22% (n = 17) in their study (whose population includes this present cohort) [8,20]. However, although the frequency of documented co-morbid psychiatric disorder was low in the Gibson study, it was higher (30%) when selfreporting.…”
Section: Discussionmentioning
confidence: 70%
“…The presentation is primarily one of sphincter disturbance, but it is often accompanied by back pain, sciatica and sensorimotor symptoms in the legs. However, about two-thirds of patients presenting with suspected clinical cauda equina syndrome have no identifiable structural cause for their symptoms 3 4…”
Section: Neurological Disease Masquerading As a Surgical Problem?mentioning
confidence: 99%
“…From recent research in two different centres, only a few (2%–7%) patients end up having an alternative neurological problem causing their symptoms,3 4 and these are typically identified during the initial admission. The number of ‘late’ presentations of alternative neurological causes is much smaller.…”
Section: Neurological Disease Masquerading As a Surgical Problem?mentioning
confidence: 99%
See 1 more Smart Citation